Parents' perspectives after stillbirth in the UK. (7th June 2011) - Schmidt, E B; Downe, S; Heazell, A E P
Abstract : Background: When a baby is stillborn, parents make difficult decisions about investigations. To offer the most effective and compassionate care, professionals must understand the range of parents' perspectives regarding investigations. Here we report the largest national survey of bereaved parents in the UK to date. This survey describes the attitudes and experiences of parents after stillbirth. Methods: Parents were invited via the Sands website and forums to complete an internet-based survey regarding their experiences after stillbirth and decisions about investigations into cause of death. Between May 2010 and January 2011, 732 responses were collected. Of those, 460 respondents' stillbirth occurred in the UK within the last 10 years. Results: 95% of respondents had some investigations to determine their child's cause of death. 62% opted for post-mortem (PM). Respondents felt that midwives and consultants had the greatest influence on their decision making. 25% of respondents felt rushed into making a decision. Respondents indicated that their heightened emotional state and separation from their child were the greatest barriers to giving consent for PM. 73% reported that their motivation for investigations was to find a reason for their child's death, while 43% wanted to aid research into causes of stillbirth. Parents who consented to PM were 2.43 times more likely to be satisfied with their decision than those who did not. Conclusions: This survey offers unique insights into parents' experiences of communication about PM and other investigations. By learning from parents' perspectives, professionals can develop strategies to provide appropriate, tailored support for parents.